Synopsis of the genus Schizachyrium Nees (Poaceae -Andropogoneae) in the State of Rio Grande do Sul, Brazil. - Welker, Cassiano Aimberê Dorneles (2012)
The genus Schizachyrium belongs to the tribe Andropogoneae and includes about 60 species distributed in tropical and subtropical regions of the world, half of which occurring in the Americas. This work consists of a survey of the species of Schizachyrium in the State of Rio Grande do Sul. Intensive ñeld collections were made in different physiographic regions of the State, as well as revision or loans from several herbaria. The occurrence of 13 species of Schizachyrium was confirmed, representing about 70% of the species of the genus in South America and 80% of the species from Brazil. This paper presents an analytical key for the identification of the species, descriptions and data on their geographical distribution, habitat and periods of flowering and fruiting, as well as illustrations of important taxonomic characters.